Genetic analysis of the Linnaean Ulva lactuca (Ulvales, Chlorophyta) holotype and related type specimens reveals name misapplications, unexpected origins, and new synonymies. Issue 3 (21st June 2019) - Hughey, Jeffery R.; Maggs, Christine A.; Mineur, Frédéric; Jarvis, Charlie; Miller, Kathy Ann; Shabaka, Soha Hamdy; Gabrielson, Paul W.
Abstract : Current usage of the name Ulva lactuca, the generitype of Ulva, remains uncertain. Genetic analyses were performed on the U. lactuca Linnaean holotype, the U. fasciata epitype, the U. fenestrata holotype, the U. lobata lectotype, and the U. stipitata lectotype. The U. lactuca holotype is nearly identical in rbc L sequence to the epitype of U. fasciata, a warm temperate to tropical species, rather than the cold temperate species to which the name U. lactuca has generally been applied. We hypothesize that the holotype specimen of U. lactuca came from the Indo‐Pacific rather than northern Europe. Our analyses indicate that U. fasciata and U. lobata are heterotypic synonyms of U. lactuca . Ulva fenestrata is the earliest name for northern hemisphere, cold temperate Atlantic and Pacific species, with U. stipitata a junior synonym. DNA sequencing of type specimens provides an unequivocal method for applying names to Ulva species.